2019
DOI: 10.1093/asj/sjz058
|View full text |Cite
|
Sign up to set email alerts
|

The Aesthetic Oculoplastic Surgery Video Teleconference Consult

Abstract: Background Skype video telemedicine consults are gaining popularity to evaluate patients from distant locations. No study has analyzed the utility of this means of patient evaluation in a cosmetic oculoplastic patient population. Objectives The authors sought to provide an evidence-based analysis of the utility of Skype video consults in a cosmetic oculoplastic surgery patient population with regards to patient demographics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Anterior Segment and Ocular Adnexa Video visits allow for at least gross examination of the ocular adnexa and anterior segment. Video visit encounters have been reported for initial patient consultation for cosmetic facial or eyelid surgery [28], and remote assessment of ptosis by photographs has good agreement with subsequent office evaluation [29].…”
Section: Visual Functionmentioning
confidence: 93%
“…Anterior Segment and Ocular Adnexa Video visits allow for at least gross examination of the ocular adnexa and anterior segment. Video visit encounters have been reported for initial patient consultation for cosmetic facial or eyelid surgery [28], and remote assessment of ptosis by photographs has good agreement with subsequent office evaluation [29].…”
Section: Visual Functionmentioning
confidence: 93%
“…These statistics complement those reported by Hwang et al, who also found a 25% conversion rate to formal in-person consultations among new patients initially seen via Skype in their cosmetic oculoplastic practices. 4 …”
Section: Discussionmentioning
confidence: 99%
“…Informed consent obligations are generally the same as those required for in-person treatment, and clinicians should adhere to the same standards of traditional office encounters. 4 Following standard-of-care practices required by federal and state laws should avoid any missteps. It is important to note that informed consent laws vary between states; some require written consent and others allow verbal consent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akin to dermatology, oculoplastic conditions are suited for telemedicine as most relevant clinical signs can be elicited without the aid of specialist equipment such as a slit lamp. Most devices used for video consultations would provide sufficient resolution for the objective assessment of oculoplastic parameters [3][4][5][6] and those examinations that cannot be conducted effectively (for example, visual acuity or optic nerve function testing) have often been conducted already by the referrer or during a previous examination.…”
mentioning
confidence: 99%